The Slr0058 Protein From Synechocystis sp. PCC 6803 Is a Novel Regulatory Protein Involved in PHB Granule Formation - Koch, Moritz; Orthwein, Tim; Alford, Janette T.; Forchhammer, Karl (Frontiers in Microbiology, 2020)
During phases of nitrogen starvation, the photosynthetic cyanobacterium Synechocystis sp. PCC 6803 produces polyhydroxybutyrate (PHB). This polymer is of high biotechnological relevance because of its potential as biodegradable plastic. Analysis of the Synechocystis genome revealed an operon (slr0058-slr0061) containing several genes, which are putatively related to the PHB metabolism. While Slr0058 show similarities with the regulatory phasin PhaF, the protein Slr0060 could serve as an intracellular PHB depolymerase. Investigation of respective knock-out mutants showed no distinct phenotype for the strain lacking Slr0060, whereas the ∆slr0058 mutant displayed a growth impairment as well as a change in pigmentation. During nitrogen starvation, the ∆slr0058 mutant produced in average more than twice the amount of PHB granules per cell, while the overall amount of PHB remained the same. This indicates that Slr0058 plays a role in PHB granule formation and controls it surface-to-volume ratio. GFP-tagged Slr0058 did not co-localize with PHB granules during nitrogen starvation but aggregated in distinct foci during vegetative growth. This work helps to better understand the PHB metabolism of Synechocystis sp. PCC 6803, coming closer to a sustainable, industrial production of PHB.